Manajemen dan Rekayasa Lalu Lintas Akibat Beroperasinya Akses Tol Tarok City - Indra Aprian Wijayayanto; Budi Hartanto Susilo; Darmawan Pontan (Jurnal Talenta Sipil, 2026)
In the construction of the Padang - Sicincin toll road, toll access is also opened which is directly connected to the national road. This toll access must be met as a form of traffic safety mitigation. This study aims to project the level of service of the intersection. And only focuses on the level of service of the intersection during the toll concession period (until 2050) and what is the ideal traffic management and engineering can be implemented at the intersection. Analysis method uses the Indonesian Road Capacity Manual (1997). Based on survey results show that in the 2025 traffic volume reaches 21,514 vehicles / day with on peak hour volume of 1,712 vehicles / hour (peak hour factor 7.9%), currently the intersection has an intersection delay of 31 SMP / Second (LoS D), these results indicate that the intersection service level exceeds the maximum limit required (25 seconds and LoS C). From the intersection’s existing performance, it is projected that the intersection performance until 2050 will have traffic growth of 4.8% - 5.2% per year. Therefore, several mitigation measures are recommended in 2025-2030 in the form of providing road equipment facilities, adjusting intersection cycle times, in 2030-2040 implementing changes to traffic cycle times, and changing traffic flow from the toll exit direction, and in 2041-2050 changing the intersection type to a non-level intersection. Based on these recommendations, the intersection service level will be 24 sec/SMP (LoS C) in 2025, 17 sec/SMP in 2030, 18 sec/SMP in 2035, 21 sec/SMP in 2040, and 24 sec/SMP in 2045. Based on the analysis results, intersection service will increase by 50% - 70% after implementing traffic management and engineering.